Plan de mercadeo para aumento de demanda del tecnicentro servilink s.a. en la ciudad de Guayaquil. - Andrade, Gabriela (2010)
There are now an active demand and a potential demand greater than supply which requires a better and excellent service. The main objective is to satisfy the requirements and demands of the customer, with excellent machinery and labor. Whereby, this project explores and analyzes two great stages: The formulation and preparation and the evaluation. Stage used to discover the problem and to find a solution through of the use of effective strategies. Therefore it has made a careful study of the variables that must be considered in the time of making investment. To analyze the requirements that consumers value when servicing your vehicle, was performed a descriptive study resulting: infrastructure, machinery and layout of the place. In also, was also carried out a complete analysis based in the financial, technical and market studies to measure the feasibility of the project and managers with these results make the decision to invest to achieve the outcomes studied. Keywords: formulation, preparation, appraisal.